2017
DOI: 10.1175/jcli-d-16-0793.1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Modulation of Precipitation Patterns over Eastern China by Sea Surface Temperature Anomalies

Abstract: Annual precipitation anomalies over eastern China are characterized by a north–south dipole pattern, referred to as the “southern flooding and northern drought” pattern (SF/ND), fluctuating on decadal time scales. Previous research has suggested possible links with oceanic forcing, but the underlying physical mechanisms by which sea surface temperature (SST) variability impacts the dipole pattern remains unclear. Idealized atmospheric general circulation model experiments conducted by the U.S. CLIVAR Drought W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 56 publications
3
78
3
Order By: Relevance
“…The PDO plays an important role in precipitation over eastern China and North America (Mantua et al, ; Barlow et al, ; Mantua and Hare, ; Chan and Zhou, ; Shen et al, ; Ma, ; Zhu et al, ; Yu, ; Chylek et al, ; Yu et al, ; Zhu et al, ; Si and Ding, ; Yang et al, ). Here, we first focus on the regression pattern of the summer precipitation onto the observation‐based PDO index and 20 CMIP5 climate models over eastern China (Figure ).…”
Section: The Model Performance Of the Pdo And Its Climatic Impactsmentioning
confidence: 97%
“…The PDO plays an important role in precipitation over eastern China and North America (Mantua et al, ; Barlow et al, ; Mantua and Hare, ; Chan and Zhou, ; Shen et al, ; Ma, ; Zhu et al, ; Yu, ; Chylek et al, ; Yu et al, ; Zhu et al, ; Si and Ding, ; Yang et al, ). Here, we first focus on the regression pattern of the summer precipitation onto the observation‐based PDO index and 20 CMIP5 climate models over eastern China (Figure ).…”
Section: The Model Performance Of the Pdo And Its Climatic Impactsmentioning
confidence: 97%
“…While previous studies (e.g., Huang et al, ) showed that the AMO has a significant influence over Inner Mongolia, our study based on dominance analysis shows that the relative dominance of the AMO is very small in this region as compared to that of the PDO, which indicates that the influence of the AMO through the Silk Route Teleconnection over Inner Mongolia is weaker than the influence of the PDO. Previous studies also showed that the positive phase of the AMO leads to the development of negative geopotential height anomalies over North China and positive geopotential height anomalies over East China, which leads to high rainfall in North China and low rainfall over East and South China regions (Si & Ding, ; Yang et al, ). In our study, the relative dominance of the AMO is found to be high for East China but low in North and South China, where the PDO shows the dominant influence (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…In East China, both the AMO and the PDO are found to have high relative dominance values (Figure a). While the positive phase of the AMO can increase the severity of droughts in East China (Si & Ding, ; Yang et al, ), the positive phase of the PDO can reduce the severity of droughts in this region via the PJ/EAP teleconnection (Qian & Zhou, ; Si & Ding, ; Zhang et al, ). Thus, the AMO and the PDO are likely to have opposing impacts on the drought severity in East China in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not apparent in the CESM-LME simulations, another noteworthy basin-scale SST forcing is the Pacific Decadal Oscillation (PDO), which has a similar multi-decadal periodicity to that of the AMO. Previous studies have indicated that the AMO and PDO, as well as 10 combinations of their different phases, may play important roles in modulating summer circulation and precipitation over eastern China on a multi-decadal timescale (e.g., Lu et al, 2006;Yu et al, 2015;Lin et al, 2016;Shi et al, 2016b;Yang et al, 2017). Nevertheless, it remains unclear how these oceanic drivers influence the EASM-precipitation relationship.…”
Section: Simulations 20mentioning
confidence: 99%